Morphometric analysis of airways in pre-COPD and mild COPD lungs using continuous surface representations of the bronchial lumen - Ortiz-Puerta, David; Diaz, Orlando; Retamal, Jaime; Hurtado, Daniel E. (Frontiers in Bioengineering and Biotechnology, 2023)
Chronic Obstructive Pulmonary Disease (COPD) is a prevalent respiratory disease that presents a high rate of underdiagnosis during onset and early stages. Studies have shown that in mild COPD patients, remodeling of the small airways occurs concurrently with morphological changes in the proximal airways. Despite this evidence, the geometrical study of the airway tree from computed tomography (CT) lung images remains underexplored due to poor representations and limited tools to characterize the airway structure. In this work, we perform a comprehensive morphometric study of the proximal airways based on geometrical measures associated with the different airway generations. To this end, we leverage the geometric flexibility of the Snakes IsoGeometric Analysis method to accurately represent and characterize the airway luminal surface and volume informed by CT images of the respiratory tree. Based on this framework, we study the airway geometry of smoking pre-COPD and mild COPD individuals. Our results show a significant difference in airway volume, length, luminal eccentricity, minimum radius, and surface-area-to-volume ratio in the most distal airways, which can be interpreted as a higher degree of airway narrowing and collapse in COPD patients. We envision that our work has the potential to deliver a comprehensive tool for assessing morphological changes in airway geometry that take place in the early stages of COPD.